Responding to Heteronormativity: Lesbian, Gay, Bisexual and Asexual Preservice Teachers’ Dreams and Fears - Bower-Phipps, Laura (Current Issues in Education, 2020)
Heteronormativity, the “privileging of heterosexuality through its normalization” (Jackson, 2006, p. 109), causes confusion and anxiety for many lesbian, gay, bisexual, and asexual preservice teachers as they consider how they will talk about their lives with students. This article explores how preservice teachers have experienced the normalization of heterosexuality and the ways in which these experiences will shape their professional practices. Focus group and follow up interviews with lesbian, gay, bisexual, and asexual preservice teachers were analyzed using a constant comparison method. Findings suggest that participants’ professional vision was largely a response to heteronormativity. They wanted to be out, be role models, and create safe spaces; yet they felt unable to achieve this vision in what they perceived as heteronormative school climates. Implications for teacher preparation programs and policies include the importance of equipping all preservice teachers to identify and disrupt heteronormativity in schools.
Keywords: dept.cur; peer-reviewed; ⛔ No DOI found